Heat Shock Proteins: Conditional Mediators of Inflammation in Tumor Immunity - Calderwood, Stuart K.; Murshid, Ayesha; Gong, Jianlin (Frontiers in Immunology, 2012)
Heat shock protein (HSP)-based anticancer vaccines have undergone successful preclinical testing and are now entering clinical trial. Questions still remain, however regarding the immunological properties of HSPs. It is now accepted that many of the HSPs participate in tumor immunity, at least in part by chaperoning tumor antigenic peptides, introducing them into antigen presenting cells such as dendritic cells (DC) that display the antigens on MHC class I molecules on the cell surface and stimulate cytotoxic lymphocytes (CTL). However, in order for activated CD8+ T cells to function as effective CTL and kill tumor cells, additional signals must be induced to obtain a sturdy CTL response. These include the expression of co-stimulatory molecules on the DC surface and inflammatory events that can induce immunogenic cytokine cascades. That such events occur is indicated by the ability of Hsp70 vaccines to induce antitumor immunity and overcome tolerance to tumor antigens such as mucin1. Secondary activation of CTL can be induced by inflammatory signaling through Toll-like receptors and/or by interaction of antigen-activated T helper cells with the APC. We will discuss the role of the inflammatory properties of HSPs in tumor immunity and the potential role of HSPs in activating T helper cells and DC licensing.